2023
DOI: 10.1111/jcmm.17716
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cyclin D1 splicing variants expression on breast cancer chemoresistance via CDK4/CyclinD1‐pRB‐E2F1 pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
(151 reference statements)
0
5
0
Order By: Relevance
“…CCND1 is a mediator of cell cycle control, and the knockdown of CCND1 splicing variants inhibits cell proliferation and prevents cell cycle progression, thus suppressing chemotherapy resistance in BC cells. 28 In BC cells, IGF1 expression is significantly increased after estrogen treatment, and IGF1 receptor inhibitors inhibit the growth of hormone-resistant BC cells. 29 In BC, SFN protects normal cells from cisplatin-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CCND1 is a mediator of cell cycle control, and the knockdown of CCND1 splicing variants inhibits cell proliferation and prevents cell cycle progression, thus suppressing chemotherapy resistance in BC cells. 28 In BC cells, IGF1 expression is significantly increased after estrogen treatment, and IGF1 receptor inhibitors inhibit the growth of hormone-resistant BC cells. 29 In BC, SFN protects normal cells from cisplatin-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified CCND1, IGF1, SFN, INHBA, TNNT1, and TNFSF11 as hub genes associated with PTX resistance in BC. CCND1 is a mediator of cell cycle control, and the knockdown of CCND1 splicing variants inhibits cell proliferation and prevents cell cycle progression, thus suppressing chemotherapy resistance in BC cells 28 . In BC cells, IGF1 expression is significantly increased after estrogen treatment, and IGF1 receptor inhibitors inhibit the growth of hormone‐resistant BC cells 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, xenograft tumor assay also confirmed that CDC42EP4 inhibited PCa cell growth in vivo. In addition, it has been reported that E-Cadherin and N-Cadherin, the marker of EMT, are closely associated with tumor invasion [ 29 , 30 ], and CyclinD1 with tumor proliferation [ 31 ]. Our data showed that PCa cells overexpressing CDC42EP4 exhibited high levels of E-cadherin and low levels of N-Cadherin and CyclinD1, suggesting that CDC42EP4 may impair the proliferative and invasive properties of PCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…This results in the unrestricted entry of free E2F into the cell nucleus, where it interacts with speci c sequences found in gene promoter regions, thereby stimulating the transcription of these genes and giving rise to abnormal cell growth and malignancy. The presence and progression of different types of tumors relies on the signi cant contribution of cyclin D1 [11][12][13][14][15]. Revised sentence: Consequently, the involvement of cyclin D1 is crucial in the onset and advancement of diverse cancer types [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The presence and progression of different types of tumors relies on the signi cant contribution of cyclin D1 [11][12][13][14][15]. Revised sentence: Consequently, the involvement of cyclin D1 is crucial in the onset and advancement of diverse cancer types [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%